Direct Imine Acylation: A Versatile Method for the Synthesis of Nitrogen-Containing Heterocycles, Spirocycles and Natural Products - Unsworth, William P.; Taylor, Richard J. K. (Synlett, 2016)
Diverse nitrogen-containing heterocyclic compounds can be synthesised by the N-acylation of imines using functionalised carboxylic acids (Direct Imine Acylation, DIA). The carboxylic acids are activated in situ using the coupling agent propylphosphonic acid anhydride (T3P), before reacting with the imine coupling partner to generate N-acyliminium ions in situ, that can then be trapped by oxygen-, nitrogen-, sulfur- or carbon-based nucleophiles built into the carboxylic acid. This versatile, convergent method has been used to generate a wide range of products, including aromatic and aliphatic heterocycles, β-lactams, azaspirocycles and natural products.1 Introduction2 DIA in the Total Synthesis of ‘Upenamide3 DIA with Benzoic Acid Derivatives4 DIA with Aliphatic Carboxylic Acids5 DIA in the Synthesis of β-Lactams6 DIA in the Synthesis of Azaspirocycles7 Mechanistic Studies8 Conclusion
Keywords: N-heterocycles; spirocycles; natural products; N-acyliminium ions; ‘upenamide; evodiamine; cavidine